A manual of naval architecture for use of officers of the Royal Navy, officers of the mercantile marine, yachtsmen, shipowners and shipbuilders - White, William Henry, 1845-1913 (John Murray, 1900)
This manual of naval architecture from 1900 includes chapters on the displacement and buoyancy of ships, the tonnage of ships, the statical stability of ships, the oscillation of ships in still water, methods of observing rolling and pitching motions of ships and deep-sea waves.
Includes index.
Keywords: Naval architecture.; elektronické knihy; electronic books